Ειδήσεις για την Ελληνική κοινότητα της Προύσας (15ος-17ος αι.) - Πατρινέλης Χ.Γ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1988)
Some new literary and documentary sources permit us to complete the rather scarce pieces of information heretofore available about the Greek community of Bursa during the 15th-17th centuries. More specifically, these new historical sources, edited and commented in this paper, are: 1) A register of subscribers to the Holy Sepulchre, dated from the years 1565-1567, and including some 57 subscribers from Bursa (Cod. Hierosol.-Patriarc. 496). 2) Two liturgical texts (synaxaries) composed by the well known scholar Manuel Corinthios (15th/16th century), and referring to two —unknown so far— Greek neo-martyrs coming from Bursa (Cod. Athon. - Iviron 512). 3) Two letters dated from Bursa, 1565, and addressed to a certain Stathis Karamanlis in Rome (Cod. Vatic, gr. 2124). The information deriving from the above mentioned texts —in combination with that of the already published sources— refer mainly to the demographic fluctations of the Greek population of Bursa during the early post- Byzantine era, to the orthodox bishopric of Bursa, to the ethnic composition of the Christian population of the town, and to various events relating to the history of the Greek community of Bursa during the period under consideration. In treating of these questions, some more general problems are also discussed, such as the islamization of Christian populations of Asia Minor, the so-called Gelali rebellion in late 16th and early 17th centuries, the migratory movement from Greece proper to Asia Minor, the massive immigration of Armenians from eastern and central Anatolia westward during the first half of the 17th century.